Testing the performance of warehousing rival policies through discrete event simulation - Silva, J.; Suleman, A.; Moreira, L. (Proceedings of the EUROMA European Operations Management Association 22nd International Annual Conference, 2015)
This research tested the performance of alternative warehouse designs concerning the picking process. Travel Distance and Total Fulfillment Time were the chosen measures. An explanatory case study was built up around a model implemented with SIMUL8. Hypotheses were set by selecting outcomes of the literature survey matching popular empirical findings. 15% reductions were found out for Total Fulfillment Time and Resource Utilisation, which was used as a proxy for operational efficiency. Literal replication of theoretical data patterns was considered as an internal validity sign. Assessing estimated changes benefits ahead of implementation was found out as a relevant contribution to practice.